A hypothesis of radioresistance and cell-survival curve shape based on cell-cycle progression and damage tolerance - Herskind, Carsten; Liu, Qi; Liu, Xiaolei; Zhang, Yingying; Ma, Lin; Angelie, Elsa; Ma, Hui Hui; Liu, Junqi; Giordano, Frank Anton; Wenz, Frederik; Veldwijk, Marlon Romano (Radiation protection dosimetry, 2019)
Exponential survival curves of early-passage humanfibroblasts challenge classic biophysical models of cell inactivation. Thus,X-ray doses of 2–4 Gy inactivate normal, human skinfibroblasts in spite of negligible residual double-strand breaks. By con-trast, radioresistant p53-mutant U251 glioblastoma cells proliferate in spite of residual damage. Similarly, p53 wildtype TK6lymphoblastoid cells show exponential survival curves while the related p53-mutant WTK1 cell line continued to proliferateand showed a shouldered survival curve. Here, we propose a model in which the radioresistant shoulder region is due to toler-ance to certain types or amounts of residual damage that would otherwise inactivate normal cells. Thus, the steeper initialslope and absence of a shoulder in the survival curve of normal cells may not imply a higher number of residual lesions butrather non-tolerance to these lesions.